PARTISIPASI MASYARAKAT TERHADAP KEHIDUPAN SOSIAL DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA BATU NANTA PADA PERIODE 2017-2022 - Suparno Suparno; Agnesia Hartini; Merri Anjelina (STKIP Persada Khatulistiwa Sintang, 2023)
This research is motivated by in Community Participation in Social Life in Infrastructure Development in Batu Nanta Village in the 2017-2022 Period. The purpose of this study is to describe how community participation is in planning, implementing, and accountability in infrastructure development in Batu Nanta Village in the 2017-2022 period, to describe how community participation is in expressing opinions and providing material in supporting infrastructure development in Batu Nanta Village in the Period 2017-2022. The research method used in this research is descriptive qualitative and the form of this research is descriptive. The results of this study indicate that: 1) The people of Batu Nanta Village are quite good at participating in the planning, implementation and accountability of infrastructure development. This is what causes social life in Batu Nanta Village to occur individual interactions with other individuals in the community, especially when the village development planning meeting is held. 2) community participation in Batu Nanta Village, namely there are two forms, namely participation in the form of giving their opinion at the MusrenbangDes, giving contributions called PADes (Original Village Income) to support infrastructure development. Keywords: community participation, social life, infrastructure development.